A blue film tape for new energy vehicle battery and preparation method thereof
By adopting a three-layer blue film tape, the photoreaction composition and photocatalyst in the UV reinforcement layer is used to solve the problem of poor curing effect when irradiated on the back of the UV, and better adhesive performance and peeling are achieved. The strength meets the use needs of power batteries under complex operating conditions.
Patent Information
- Application Number
- CN202411426320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing blue film tape has poor curing effect when exposed to the back of the UV, resulting in poor bonding performance and cannot fully meet the use needs of power batteries under complex operating conditions.
A three-layer blue film tape is used, the outer layer is a PET release film, the middle layer is a UV reinforcement layer, and the inner layer is a blue PVC substrate film. The raw materials of the UV reinforcement layer include polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreaction composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier, through the photocatalyst and the curing agent. Curing reaction strengthens the cohesive strength of the glue layer and improves the adhesive performance.
Through moderate back irradiation, the glue layer undergoes partial curing reaction, resulting in good adhesion properties, and the glue layer is firmly wrapped around the battery cell shell. The fully cured blue film tape obtains excellent peel strength and shear strength, which can better solve the problem of fixing the battery pack.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of adhesive tape technology, and more specifically, to a blue film adhesive tape for new energy vehicle batteries and a preparation method thereof. Background Art
[0002] As an important material for battery insulation and fixation protection, blue film tape has good insulation properties, can separate cells from each other, and prevent a single cell from affecting other cells due to failure; it has excellent chemical resistance and tensile strength, and can adapt to the use of power batteries in various complex environments; it also has the characteristics of direct bonding and convenient operation, which can improve the production efficiency of power batteries. The application of blue film tape in new energy vehicle batteries mainly includes power battery assembly insulation protection and fixation, cylindrical / square power battery pack bundling, etc.; by wrapping and fixing the battery pack, it plays an insulating and protective role, ensuring the safety and stability of the battery pack during use.
[0003] Although blue film tape plays an important role in insulating, fixing and protecting batteries, it also has some shortcomings. Because the blue film is colored, if the front irradiation method is used, the light cannot penetrate, so UV curing cannot be used; however, if the back irradiation method is used, when the back irradiation time is too long, the curing is thorough, causing the adhesive surface to harden, and the fluidity and adhesion of the adhesive layer are reduced, which is not conducive to subsequent winding and fixing; when the back irradiation time is too short, the curing is insufficient; therefore, it is currently impossible to control the back irradiation time well, resulting in relatively limited adhesive properties of the back adhesive of the blue film tape, which in turn causes the blue film tape to be unable to fully meet the use requirements of power batteries under complex working conditions, especially when subjected to external force impact, the structural adhesive may fall off the blue film, or the back adhesive of the blue film may undergo cohesive failure, causing the blue film to fall off and peel off from the battery cell shell, thereby affecting the safety and stability of the battery.
[0004] Based on the above statements, the present invention proposes a blue film tape for new energy vehicle batteries and a preparation method thereof. Summary of the invention
[0005] In order to solve the problem that the existing blue film tape has poor curing effect and poor bonding performance when UV back irradiation is used, the present invention provides a blue film tape for new energy vehicle batteries and a preparation method thereof.
[0006] In the first aspect, the present invention provides a blue film tape for new energy vehicle batteries, which adopts the following technical solution:
[0007] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, wherein the outer layer is a PET release film with a thickness of 45-55 μm; the middle layer is a UV enhancement layer with a thickness of 50-60 μm; and the inner layer is a blue PVC base film with a thickness of 45-55 μm;
[0008] The UV enhancement layer comprises the following raw materials in parts by weight: 100-200 parts of polyacrylate, 30-60 parts of polyester, 20-40 parts of polyurethane, 20-50 parts of ethylene-vinyl acetate copolymer, 10-40 parts of photoreactive composition, 5-10 parts of photocatalyst, 20-40 parts of curing agent, 5-20 parts of filler, 1-3 parts of anti-aging agent and 1-10 parts of tackifier.
[0009] Preferably, the photoreactive composition is obtained by mixing halloysite nanotube-loaded thiol ionic liquid, dithiothreitol and isophytol in a mass ratio of 10:3-5:1-2.
[0010] Preferably, the photoreactive composition is obtained by mixing halloysite nanotube-loaded thiol ionic liquid, dithiothreitol and isophytol in a mass ratio of 10:3:2.
[0011] Preferably, the preparation method of the halloysite nanotube-loaded thiol ionic liquid is as follows:
[0012] Add halloysite nanotubes and 4-(chloromethyl)phenyltrimethoxysilane to N,N-dimethylformamide, stir evenly, add 3-(pyridin-2-yl)propane-1-thiol, react at 120-130° C. for 24-36 hours, cool to room temperature, vacuum filter, and wash the filter cake with ethanol;
[0013] The filter cake is added into a sodium hydroxide aqueous solution, reacted at room temperature for 12-24 hours, filtered, washed with water until the filtrate is neutral, and vacuum dried to obtain a halloysite nanotube-loaded thiol ionic liquid.
[0014] Preferably, the ratio of the halloysite nanotubes, 4-(chloromethyl)phenyltrimethoxysilane, N,N-dimethylformamide, and 3-(pyridin-2-yl)propane-1-thiol is 0.1-1 g:20-40 mmol:50 mL:20-30 mmol.
[0015] Preferably, the concentration of the sodium hydroxide aqueous solution is 1-2 mol / L, and the volume is 30-40 mL.
[0016] Preferably, the inner diameter of the halloysite nanotube is 12-20 nm, the outer diameter is 50-70 nm, and the length is 0.5-1 μm.
[0017] Preferably, the photocatalyst is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, benzil dimethyl ether, benzophenone and 2-isopropylthioxanthone.
[0018] Preferably, the curing agent is a cationic curing agent; the cationic curing agent is at least one of tetraethylamine hydrochloride, sodium hexafluoroantimonate, ethyltriphenylammonium bromide and triisopropanolamine cyclic borate.
[0019] Preferably, the filler is at least one of nano silicon dioxide, nano titanium dioxide, nano calcium carbonate, nano aluminum oxide, nano lanthanum oxide and nano cerium oxide.
[0020] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, and antioxidant 1135.
[0021] Preferably, the tackifier is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2-8:5.
[0022] In a second aspect, the present invention provides a method for preparing a blue film tape for a new energy vehicle battery, using the following technical solution:
[0023] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0024] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0025] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0026] S3. Bake the semi-finished product at 70-80° C. for 5-10 min, and then mature it at 50-60° C. for 48-72 h to obtain a blue film tape.
[0027] In summary, the present invention has the following beneficial effects:
[0028] 1. The blue film tape for new energy vehicle batteries of the present invention comprises a three-layer structure, wherein the outer layer is a PET release film, the middle layer is a UV enhancement layer, and the inner layer is a blue PVC substrate film; and the raw materials of the UV enhancement layer include polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent, and tackifier, with polyacrylate, polyester, polyurethane, and ethylene-vinyl acetate copolymer as the main resin to provide initial strength and operability; the photoreactive composition is fully compatible with the main resin to provide UV enhancement function; the photocatalyst and the curing agent are used for curing reaction to strengthen the cohesive strength of the adhesive layer and improve the bonding performance of the blue film tape; at the same time, fillers, anti-aging agents, and tackifiers are added as auxiliary agents; the present invention strictly controls the ratio of the raw materials of the UV enhancement layer, and when the blue film tape is appropriately irradiated from the back, the adhesive layer will undergo a partial curing reaction to produce good bonding performance, so that the adhesive layer is firmly wrapped around the battery cell shell, and then continues to cure through a dark reaction; the fully cured blue film tape obtains excellent peel strength and shear strength, which can better solve the problem of fixing the battery pack.
[0029] 2. The photoreaction composition of the present invention can undergo a thiol-ene click chemical reaction under the action of a photocatalyst, thereby increasing the internal network density of the UV enhancement layer and improving the cohesive force; and the photoreaction composition is obtained by mixing a specific proportion of halloysite nanotube-loaded thiol ionic liquid, dithiothreitol and isophytol, and the three synergistically enhance the effect, which can well regulate the photocuring process of UV backlight irradiation to avoid excessive photocuring, and can effectively ensure the fluidity and adhesion of the adhesive layer, which is conducive to better winding and fixing of the subsequent blue film tape.
[0030] 3. The present invention connects halloysite nanotubes and 3-(pyridin-2-yl)propane-1-thiol through 4-(chloromethyl)phenyltrimethoxysilane to form halloysite nanotube-loaded thiol ionic liquid. The halloysite nanotube-loaded thiol ionic liquid can not only participate in the UV curing reaction, but also serve as a rigidity enhancer to enhance the mechanical properties of the UV enhancement layer. At the same time, in the UV curing system, the halloysite nanotube-loaded thiol ionic liquid can preferentially capture UV light particles and generate sufficient active free radicals, one part of which is used for the first photocuring reaction and the other part is used to trigger the subsequent dark reaction, thereby effectively controlling the UV curing process. In addition, the halloysite nanotubes with a unique nanotube cavity structure combined with the loaded thiol ionic liquid greatly reduce the influence of oxygen inhibition, are easier to release shrinkage stress, and will not cause volume changes in the UV enhancement layer, thereby ensuring that the blue film tape has a higher shear strength after curing.
[0031] 4. The present invention uses butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane as tackifiers. The two interact and assist each other, and the crosslinking density of the UV enhancement layer is further increased, thereby enhancing the bonding strength of the UV enhancement layer, and can effectively and timely compensate for the viscosity loss problem in the UV curing process, thereby further improving the bonding performance of the blue film tape.
[0032] 5. In the preparation process of the blue film tape, the present invention controls various process parameters to promote the interaction between the components, thereby improving the bonding performance of the blue film tape. The preparation method has simple steps, low cost, and is suitable for industrial production. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with reference to the embodiments.
[0034] The materials and reagents used in the present invention, unless otherwise specified, can be obtained from commercial sources; among them, 4-(chloromethyl)phenyltrimethoxysilane, CAS No. 24413-04-5, was purchased from Shanghai Yuanye Biotechnology Co., Ltd. (purity 95%); 3-(pyridin-2-yl)propane-1-thiol, CAS No. 1022507-42-1, was purchased from Shanghai Haohong Biomedical Technology Co., Ltd. (purity 95%); polyacrylate, CAS No. 31759-42-9, was purchased from Jinjin Le Chemical Co., Ltd.; polyester, CAS No. 113669-95-7, purchased from Shanghai Koraman Reagent Co., Ltd. (brand: Kramar); polyurethane, CAS No. 26680-22-8, purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd. (purity 99%); ethylene-vinyl acetate copolymer, CAS No. 24937-78-8, purchased from Shanghai Yuanye Biotechnology Co., Ltd. (vinyl acetate 12wt%, melt index 8g / 10min (190℃ / 2.16kg)).
[0035] Preparation Example 1:
[0036] The preparation method of the halloysite nanotube-loaded thiol ionic liquid is as follows:
[0037] 0.1 g of halloysite nanotubes (the inner diameter of the halloysite nanotubes is 12-20 nm, the outer diameter is 50-70 nm, and the length is 0.5-1 μm) and 20 mmol of 4-(chloromethyl)phenyltrimethoxysilane are added to 50 mL of N,N-dimethylformamide, and after stirring evenly, 20 mmol of 3-(pyridin-2-yl)propane-1-thiol is added, and the mixture is reacted at 120° C. for 36 h, cooled to room temperature, vacuum filtered, and the filter cake is washed with ethanol;
[0038] The filter cake was added into 30 mL of 2 mol / L sodium hydroxide aqueous solution, reacted at room temperature for 24 h, filtered, washed with water until the filtrate was neutral, and vacuum dried to obtain halloysite nanotube-loaded thiol ionic liquid.
[0039] Preparation Example 2:
[0040] The preparation method of the halloysite nanotube-loaded thiol ionic liquid is as follows:
[0041] 0.5 g of halloysite nanotubes (the inner diameter of the halloysite nanotubes is 12-20 nm, the outer diameter is 50-70 nm, and the length is 0.5-1 μm) and 30 mmol of 4-(chloromethyl)phenyltrimethoxysilane are added to 50 mL of N,N-dimethylformamide, and after stirring evenly, 25 mmol of 3-(pyridin-2-yl)propane-1-thiol is added, and the mixture is reacted at 125° C. for 30 h, cooled to room temperature, vacuum filtered, and the filter cake is washed with ethanol;
[0042] The filter cake was added into 35 mL of 1.5 mol / L sodium hydroxide aqueous solution, reacted at room temperature for 20 h, filtered, washed with water until the filtrate was neutral, and vacuum dried to obtain halloysite nanotube-loaded thiol ionic liquid.
[0043] Preparation Example 3:
[0044] The preparation method of the halloysite nanotube-loaded thiol ionic liquid is as follows:
[0045] 1 g of halloysite nanotubes (the inner diameter of the halloysite nanotubes is 12-20 nm, the outer diameter is 50-70 nm, and the length is 0.5-1 μm) and 40 mmol of 4-(chloromethyl)phenyltrimethoxysilane are added to 50 mL of N,N-dimethylformamide, stirred evenly, and then 30 mmol of 3-(pyridin-2-yl)propane-1-thiol is added, reacted at 130° C. for 24 h, cooled to room temperature, vacuum filtered, and the filter cake was washed with ethanol;
[0046] The filter cake was added into 40 mL of 1 mol / L sodium hydroxide aqueous solution, reacted at room temperature for 12 h, filtered, washed with water until the filtrate was neutral, and vacuum dried to obtain halloysite nanotube-loaded thiol ionic liquid.
[0047] Embodiment 1-5 provides a blue film tape for new energy vehicle batteries and a preparation method thereof.
[0048] Embodiment 1:
[0049] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0050] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0051] The photoreaction composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:3:1, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano-silicon dioxide and nano-lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2:5;
[0052] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0053] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0054] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0055] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0056] Embodiment 2:
[0057] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 50 μm; a middle layer of a UV enhancement layer with a thickness of 55 μm; and an inner layer of a blue PVC base film with a thickness of 50 μm;
[0058] The UV enhancement layer comprises the following raw materials in parts by weight: 120 parts of polyacrylate, 35 parts of polyester, 35 parts of polyurethane, 45 parts of ethylene-vinyl acetate copolymer, 20 parts of photoreactive composition, 7 parts of photocatalyst, 25 parts of curing agent, 10 parts of filler, 1.5 parts of anti-aging agent, and 3 parts of tackifier;
[0059] The photoreaction composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:3:1.5, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 2; the photocatalyst is obtained by mixing 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone and benzil dimethyl ether in a mass ratio of 1:2; the curing agent is ethyl triphenylammonium bromide; the filler is obtained by mixing nano silicon dioxide, nano titanium dioxide and nano cerium oxide in a mass ratio of 1:2:1; the anti-aging agent is obtained by mixing antioxidant 1010, antioxidant 1076 and antioxidant 1098 in a mass ratio of 1:1:1; the tackifier is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 4:5;
[0060] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0061] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0062] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0063] S3. Bake the semi-finished product at 72° C. for 8 min, and then mature it at 52° C. for 64 h to obtain a blue film tape.
[0064] Embodiment 3:
[0065] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 50 μm; a middle layer of a UV enhancement layer with a thickness of 55 μm; and an inner layer of a blue PVC base film with a thickness of 50 μm;
[0066] The UV enhancement layer comprises the following raw materials in parts by weight: 150 parts of polyacrylate, 450 parts of polyester, 30 parts of polyurethane, 35 parts of ethylene-vinyl acetate copolymer, 25 parts of photoreactive composition, 7.5 parts of photocatalyst, 30 parts of curing agent, 10 parts of filler, 2 parts of anti-aging agent, and 5 parts of tackifier;
[0067] The photoreaction composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:4:1, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 3; the photocatalyst is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the curing agent is obtained by mixing sodium hexafluoroantimonate and triisopropanolamine cyclic borate in a mass ratio of 1:1; the filler is obtained by mixing nano-alumina and nano-lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is obtained by mixing antioxidant 1098 and antioxidant 1135 in a mass ratio of 1:1; the tackifier is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 8:5;
[0068] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0069] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0070] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0071] S3. Bake the semi-finished product at 78° C. for 7 minutes, and then mature it at 58° C. for 56 hours to obtain a blue film tape.
[0072] Embodiment 4:
[0073] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 55 μm; a middle layer of a UV enhancement layer with a thickness of 50 μm; and an inner layer of a blue PVC base film with a thickness of 55 μm;
[0074] The UV enhancement layer comprises the following raw materials in parts by weight: 180 parts of polyacrylate, 50 parts of polyester, 25 parts of polyurethane, 25 parts of ethylene-vinyl acetate copolymer, 35 parts of photoreactive composition, 8 parts of photocatalyst, 35 parts of curing agent, 15 parts of filler, 2.5 parts of anti-aging agent, and 8 parts of tackifier;
[0075] The photoreaction composition is obtained by mixing halloysite nanotube-loaded thiol ionic liquid, dithiothreitol and isophytol in a mass ratio of 10:3:2, and the halloysite nanotube-loaded thiol ionic liquid is prepared by Preparation Example 1; the photocatalyst is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the curing agent is ethyltriphenylammonium bromide; the filler is nano-lanthanum oxide; the anti-aging agent is antioxidant 1010; the viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 8:5;
[0076] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0077] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0078] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0079] S3. Bake the semi-finished product at 78° C. for 6 min, and then mature it at 58° C. for 52 h to obtain a blue film tape.
[0080] Embodiment 5:
[0081] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 55 μm;
[0082] The UV enhancement layer comprises the following raw materials in parts by weight: 200 parts of polyacrylate, 60 parts of polyester, 20 parts of polyurethane, 20 parts of ethylene-vinyl acetate copolymer, 40 parts of photoreactive composition, 10 parts of photocatalyst, 40 parts of curing agent, 20 parts of filler, 3 parts of anti-aging agent, and 10 parts of tackifier;
[0083] The photoreaction composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:5:2, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 2; the photocatalyst is obtained by mixing 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone and benzil dimethyl ether in a mass ratio of 1:1:1; the curing agent is obtained by mixing a thiol ionic liquid loaded on the halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:5:2, and the halloysite nanotubes are prepared by Preparation Example 2; the photocatalyst is obtained by mixing 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)- The filler is obtained by mixing nano silicon dioxide, nano calcium carbonate, nano aluminum oxide and nano cerium oxide in a mass ratio of 1:1:1; the anti-aging agent is obtained by mixing antioxidant 1010 and antioxidant 1098 in a mass ratio of 1:1; the tackifier is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 8:5;
[0084] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0085] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0086] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0087] S3, baking the semi-finished product at 80°C for 5 minutes, and then aging it at 60°C for 48 hours to obtain a blue film tape.
[0088] In order to verify the performance of the blue film tape for new energy vehicle batteries obtained in Examples 1-5 of the present invention, the present invention sets up Comparative Examples 1-6.
[0089] Comparative Example 1:
[0090] Comparative Example 1 is different from Example 1 only in that an equal mass of 3-(pyridin-2-yl)propane-1-thiol is used to replace the halloysite nanotube-loaded thiol ionic liquid, as follows:
[0091] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0092] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0093] The photoreactive composition is obtained by mixing 3-(pyridin-2-yl)propane-1-thiol, dithiothreitol and isophytol in a mass ratio of 10:3:1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano silicon dioxide and nano lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2:5;
[0094] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0095] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0096] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0097] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0098] Comparative Example 2:
[0099] Comparative Example 2 is different from Example 1 only in that the photoreactive composition is obtained by mixing the halloysite nanotube-loaded thiol ionic liquid and dithiothreitol in a mass ratio of 10:3, as follows:
[0100] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0101] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0102] The photoreactive composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes and dithiothreitol in a mass ratio of 10:3, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano-silicon dioxide and nano-lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2:5;
[0103] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0104] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0105] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0106] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0107] Comparative Example 3:
[0108] Comparative Example 3 is different from Example 1 only in that the photoreactive composition is obtained by mixing the halloysite nanotube-loaded thiol ionic liquid and isophytol in a mass ratio of 10:1, as follows:
[0109] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0110] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0111] The photoreaction composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes and isophytol in a mass ratio of 10:1, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano-silicon dioxide and nano-lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2:5;
[0112] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0113] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0114] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0115] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0116] Comparative Example 4:
[0117] Comparative Example 4 is different from Example 1 only in that the photoreactive composition is obtained by mixing dithiothreitol and isophytol in a mass ratio of 3:1, as follows:
[0118] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0119] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0120] The photoreaction composition is obtained by mixing dithiothreitol and isophytol in a mass ratio of 3:1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano silicon dioxide and nano lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2:5;
[0121] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0122] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0123] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0124] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0125] Comparative Example 5:
[0126] Comparative Example 5 is different from Example 1 only in that the tackifier is only butyl titanate, as follows:
[0127] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0128] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0129] The photoreaction composition is obtained by mixing the thiol ionic liquid loaded on the halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:3:1, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano-silicon dioxide and nano-lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is butyl titanate;
[0130] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0131] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0132] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0133] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0134] Comparative Example 6:
[0135] Comparative Example 6 is different from Example 1 only in that the tackifier is only N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, specifically as follows:
[0136] A blue film tape for new energy vehicle batteries, comprising a three-layer structure, an outer layer of a PET release film with a thickness of 45 μm; a middle layer of a UV enhancement layer with a thickness of 60 μm; and an inner layer of a blue PVC base film with a thickness of 45 μm;
[0137] The UV enhancement layer comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyester, 40 parts of polyurethane, 50 parts of ethylene-vinyl acetate copolymer, 10 parts of photoreactive composition, 5 parts of photocatalyst, 20 parts of curing agent, 5 parts of filler, 1 part of anti-aging agent, and 1 part of tackifier;
[0138] The photoreaction composition is obtained by mixing a thiol ionic liquid loaded on halloysite nanotubes, dithiothreitol and isophytol in a mass ratio of 10:3:1, and the thiol ionic liquid loaded on the halloysite nanotubes is prepared by Preparation Example 1; the photocatalyst is 1-hydroxycyclohexyl phenyl ketone; the curing agent is tetraethylamine hydrochloride; the filler is obtained by mixing nano-silicon dioxide and nano-lanthanum oxide in a mass ratio of 1:1; the anti-aging agent is antioxidant 1010; the viscosity enhancer is N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane;
[0139] A method for preparing a blue film tape for a new energy vehicle battery comprises the following steps:
[0140] S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material;
[0141] S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product;
[0142] S3. Bake the semi-finished product at 70° C. for 10 min, and then mature it at 50° C. for 72 h to obtain a blue film tape.
[0143] Performance testing:
[0144] The blue film tapes obtained in Examples 1-5 of the present invention and Comparative Examples 1-6 were subjected to performance tests, and the results are shown in Table 1:
[0145] After the blue film tape was irradiated by 2000mj 365nm LED, it was bonded to the aluminum plate within 2 minutes, and the structural adhesive was used for bonding after 1 day. After 7 days at room temperature, the shear strength of the tape was tested with reference to GB / T 33332-2016 "Test method for dynamic shear strength of adhesive tape";
[0146] Refer to GB / T2792-2014 "Test method for peel strength of adhesive tape" to test the peel strength of the tape before UV, 20 minutes after UV, and after full curing;
[0147] Refer to GB / T4852-2002 "Test method for initial tack of pressure-sensitive adhesive tapes (rolling ball method)" to test the initial tack of the tape after full curing;
[0148] Refer to GB / T4851-2014 "Test method for holding strength of adhesive tape" to test the holding strength of the tape after full curing.
[0149] Table 1:
[0150]
[0151] From the data shown in Table 1 above, it can be seen that the comprehensive performance of the blue film tape obtained in Examples 1-5 is significantly better than that in Comparative Examples 1-6. The blue film tape has high initial tack and good sustained tack, and has UV tackifying function. After backlight irradiation, the peel strength is gradually enhanced, and the shear strength after curing is relatively high, which fully demonstrates that the blue film tape of the present invention can achieve excellent product adhesion, heavy workability and stability, and can be widely used in new energy vehicle batteries.
[0152] It can be seen from Example 1 and Comparative Example 1 that the present invention loads 3-(pyridin-2-yl)propane-1-thiol onto halloysite nanotubes to form halloysite nanotube-loaded thiol ionic liquid, which can significantly improve the peel strength of the blue film tape after UV curing, and the shear strength of the blue film tape is also greatly improved.
[0153] It can be seen from Example 1 and Comparative Examples 2-4 that the photoreactive composition of the present invention is obtained by mixing halloysite nanotubes loaded with thiol ionic liquid, dithiothreitol and isophytol, and the three synergistically enhance the peel strength and shear strength of the blue film tape.
[0154] It can be seen from Example 1 and Comparative Examples 5 and 6 that the tackifier of the present invention is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and the two assist each other, which is beneficial to improving the peel strength and shear strength of the blue film tape and enhancing the initial adhesion and lasting adhesion of the blue film tape.
[0155] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A blue film tape for new energy vehicle batteries, characterized in that: It includes a three-layer structure, the outer layer is a PET release film with a thickness of 45-55μm; the middle layer is a UV enhancement layer with a thickness of 50-60μm; the inner layer is a blue PVC base film with a thickness of 45-55μm; The UV enhancement layer comprises the following raw materials in parts by weight: 100-200 parts of polyacrylate, 30-60 parts of polyester, 20-40 parts of polyurethane, 20-50 parts of ethylene-vinyl acetate copolymer, 10-40 parts of photoreactive composition, 5-10 parts of photocatalyst, 20-40 parts of curing agent, 5-20 parts of filler, 1-3 parts of anti-aging agent, and 1-10 parts of tackifier; The photoreactive composition is obtained by mixing halloysite nanotubes loaded with thiol ionic liquid, dithiothreitol and isophytol in a mass ratio of 10:3-5:1-2; The preparation method of the halloysite nanotube-loaded thiol ionic liquid is as follows: Add halloysite nanotubes and 4-(chloromethyl)phenyltrimethoxysilane to N,N-dimethylformamide, stir evenly, add 3-(pyridin-2-yl)propane-1-thiol, react at 120-130° C. for 24-36 hours, cool to room temperature, vacuum filter, and wash the filter cake with ethanol; The filter cake is added to a sodium hydroxide aqueous solution, reacted at room temperature for 12-24 hours, filtered, washed with water until the filtrate is neutral, and vacuum dried to obtain a halloysite nanotube-loaded thiol ionic liquid; The viscosity enhancer is obtained by mixing butyl titanate and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane in a mass ratio of 2-8:
5.
2. The blue film tape for new energy vehicle batteries according to claim 1, characterized in that: The photoreaction composition is obtained by mixing halloysite nanotube-loaded thiol ionic liquid, dithiothreitol and isophytol in a mass ratio of 10:3:
2.
3. The blue film tape for new energy vehicle batteries according to claim 1, characterized in that: The ratio of the amount of the halloysite nanotube, 4-(chloromethyl)phenyltrimethoxysilane, N,N-dimethylformamide, and 3-(pyridin-2-yl)propane-1-thiol is 0.1-1 g: 20-40 mmol: 50 mL: 20-30 mmol; The concentration of the sodium hydroxide aqueous solution is 1-2 mol / L, and the volume is 30-40 mL.
4. The blue film tape for new energy vehicle batteries according to claim 1, characterized in that: The inner diameter of the halloysite nanotube is 12-20 nm, the outer diameter is 50-70 nm, and the length is 0.5-1 μm.
5. The blue film tape for new energy vehicle batteries according to claim 1, characterized in that: The photocatalyst is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, benzil dimethyl ether, benzophenone and 2-isopropylthioxanthone; The curing agent is a cationic curing agent; the cationic curing agent is at least one of tetraethylamine hydrochloride, sodium hexafluoroantimonate, ethyltriphenylammonium bromide and triisopropanolamine cyclic borate.
6. The blue film tape for new energy vehicle batteries according to claim 1, characterized in that: The filler is at least one of nano silicon dioxide, nano titanium dioxide, nano calcium carbonate, nano aluminum oxide, nano lanthanum oxide and nano cerium oxide; The antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, and antioxidant 1135.
7. A method for preparing the blue film tape for new energy vehicle batteries according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. According to the formula of the UV enhancement layer, polyacrylate, polyester, polyurethane, ethylene-vinyl acetate copolymer, photoreactive composition, photocatalyst, curing agent, filler, anti-aging agent and tackifier are mixed to obtain a mixed material; S2, first coating the mixed material on a blue PVC substrate film to form a UV enhancement layer, and then laminating a PET release film on the other side of the UV enhancement layer to obtain a semi-finished product; S3. Bake the semi-finished product at 70-80° C. for 5-10 min, and then mature it at 50-60° C. for 48-72 h to obtain a blue film tape.
Citation Information
Patent Citations
High-temperature-resistant high-shear UV (ultraviolet) blue film adhesive for protecting battery cell and blue film
CN117050691A
Cited By
High-weather-resistance PVC adhesive tape composite material and preparation method thereof
CN120966383A